Influence of Light on phytoplankton growth in Lattakia coastal water - درويش, فيروز (Latakia University Journal -Biological Sciences Series, 2022)
In this research, the phytoplankton behavior has been investigated in a Mesocosm experiments to clarify changes in their growth under different light conditions (NO3, PO4& SiO4). The amount of nutrient consumed by phytoplankton was studied, and the changes in Chla concentration with determining phytoplankton specific composition were identified.In the experiments that have been conducted during January. 2020, Diatoms were able to grow in the media where the severity of the lighting have been mitigated, and accompanied by doubling the initial concentrations under light limiting condition, which then continued growing in nutrients enriched media despite the different lighting conditions.Centric diatoms were prevailed in the experiments carried out during 2020, particularly some species of the genera: Chaetoceros and Thalassiosira, which were able to grow in nutrient enriched media even under the influence of light limiting conditions. The results showed that nutrients not light limited the growth of phytoplankton during winter in studied area. Keywords: diatoms, light, enrichment experiment, nutrients, phytoplankton